NOMINATION AND SEMANTICS OF CLOTHING: DENOTATIVE AND CONNOTATIVE COMPONENTS, EVALUATIVENESS, AND EXPRESSIVENESS (SCIENCE TIME JOURNAL, 2026)
The article examines the nomination and semantics of clothing vocabulary in English. Particular attention is given to the interaction of denotative and connotative components of meaning, as well as to evaluativeness and expressiveness in clothing-related lexical units. The study is based on semantic and contextual analysis and demonstrates that clothing vocabulary reflects not only the physical characteristics of garments but also social, cultural, and emotional meanings.